Effects of habitat fragmentation on the reproductive ecology and conservation genetics of the almendro (Dipteryx panamensis), a keystone rainforest tree - Hanson, Thor (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), University of Idaho, Moscow, ID (EUA), 2014)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho